2019
DOI: 10.1371/journal.pcbi.1006741
|View full text |Cite
|
Sign up to set email alerts
|

Spatial synchronization codes from coupled rate-phase neurons

Abstract: During spatial navigation, the frequency and timing of spikes from spatial neurons including place cells in hippocampus and grid cells in medial entorhinal cortex are temporally organized by continuous theta oscillations (6–11 Hz). The theta rhythm is regulated by subcortical structures including the medial septum, but it is unclear how spatial information from place cells may reciprocally organize subcortical theta-rhythmic activity. Here we recorded single-unit spiking from a constellation of subcortical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 90 publications
(143 reference statements)
2
30
0
Order By: Relevance
“…While the phenomenon is less clear in open, 2-dimensional environments, phase precession has been observed in particular traversals of the firing fields of place cells as well as grid cells in entorhinal cortex (Climer et al, 2013;Jeewajee et al, 2014). However, our analysis of phaser cells in the lateral septum (Monaco et al, 2019a) revealed a more direct phase code for 2-dimensional position that was consistent with a minimal model of temporal phase-coding ( Fig. 1C).…”
Section: Hippocampal Model Mechanismssupporting
confidence: 81%
See 3 more Smart Citations
“…While the phenomenon is less clear in open, 2-dimensional environments, phase precession has been observed in particular traversals of the firing fields of place cells as well as grid cells in entorhinal cortex (Climer et al, 2013;Jeewajee et al, 2014). However, our analysis of phaser cells in the lateral septum (Monaco et al, 2019a) revealed a more direct phase code for 2-dimensional position that was consistent with a minimal model of temporal phase-coding ( Fig. 1C).…”
Section: Hippocampal Model Mechanismssupporting
confidence: 81%
“…A weakness of the presented implementation was the use of a global, shared oscillation without allowing for noise, drift, or independent perturbations (cf. Zilli and Hasselmo, 2010;Monaco et al, , 2019a. A more decentralized approach might utilize resonant agent-oscillators that self-organize local oscillations depending on available information, task requirements, or context.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another review article on the similarities and differences in the hippocampus between rodents and primates [48] was important research but was excluded in this paper to focus on rodents. An article on "phaser cells" and their simulation [49] was also excluded because phaser cells were discovered mainly in the medial septum that is related to the hippocampus. As a result, three articles [50][51][52] were left out of 11 papers.…”
Section: Methodsmentioning
confidence: 99%